Smoking Habit Prevention in Schools: Report of a Pediatric Educational Intervention Held in Pisa - Bellino, Elisabetta M.; Di Cicco, Maria; Soldateschi, Massimo; Frangione, Lucia; Rosati, Sara; Tyutyusheva, Nina; Angelucci, Claudia; Maiorino, Giuseppe; D’Elios, Sofia; Piccigallo, Adriana; Peroni, Diego (International Journal of Pediatrics and Child Health, 2020)
Introduction: Smoking is the leading preventable cause of death in the world and the detrimental effects of tobacco on health have been described across the full life span. There is no safe level of tobacco exposure and childhood is the more vulnerable period of life. Current estimates show that 10% of children aged 13-15 years are active smokers and most of them started smoking at >11 years of age, due to peer and/or family influence. Moreover, recently, e-cigarette use has spread, particularly among youth. Many school-based smoking prevention interventions have been carried out around the world, the efficacy of which has yet to be established. Materials and methods: In February 2018 we planned an educational program on smoking habit within the Italian Society of Pediatric Respiratory Diseases (SIMRI) (“Dai un calcio al fumo” program). In May 2018 we held 8 interventions at the Fibonacci School (Pisa, Italy), meeting 365 children aged 9 to 13 years and involving a pediatrician and a pediatric resident in a 2-hour lesson focusing on the importance of a healthy lifestyle and smoking habit effects. The children were invited to ask questions and talk about their experiences, with a subsequent 30-minutes collegial discussion. The most frequent questions were collected, as well as students’, physicians’ and teachers’ opinions on each meeting. Results: During our educational interventions the most frequently asked questions were about the discrepancy related to the fact that a dangerous product is legally sold and the potential harmful effects of e-cigarettes. All the children stated that they knew that combustible cigarette smoking was dangerous. Most of them admitted that they feel that smoking habits start from emulating friends and relatives. Almost 70% of the children reported to have at least one smoker relative. Teachers, physicians and students proposed to replicate the meetings the following year. Conclusions: The considerable interest shown by the students, together with the low cost and potential effectiveness of school-based educational measures, suggest that in our country a national educational program should be introduced in schools. Too many children are still exposed to tobacco smoke in the household environment.